IMPLEMENTATION BASED INSTRUCTIONAL MATERIALS CONTEXTUAL TEACHING AND LEARNING (CTL) IN MATHEMATICS LEARNING HIGH SCHOOL STUDENTS - Anggria Septiani Mulbasari; Nora Surmilasari (Sriwijaya University Learning and Education International Conference, 2018)
Generally, this study aims to determine how the application-based teaching materials Contextual Teaching and Learning (CTL) on the high school math learning. In particular, this study aims to describe the activities of the students when learning using CTL-based teaching materials. In this study the material being taught is a matter of multiplication, permutations and combinations. This research is qualitative research subjects are students of class XI IPA 6 SMAN 8 Palembang total of 36 students. The results of this study demonstrate that CTL-based teaching material can be applied to high school students for math learning activities the students during learning using CTL teaching materials included in either category.